Roadmap to the Implementation of Best Practices in Human Factors Voluntary Reporting for Safety. - Darveau, Katherine. (2017)
Abstract: Federal agencies responsible for defining standards in high-risk industries (such as aviation, rail, and healthcare) promote voluntary reporting of personally committed errors and violations as a way to meet safety management system requirements. Although voluntary reporting systems are valuable tools for uncovering error causal factors, they are often underutilized. This thesis identified barriers and facilitators to effective voluntary reporting practices through a literature review and interviews with industry professionals. Identified barriers include insufficient organizational commitment to safety culture, lack of user trust in voluntary reporting systems and in management, unclear system policy and procedure definition, inadequate training techniques, and ineffective use of voluntary reports to implement meaningful solutions. Following the identification of these barriers, a questionnaire was distributed to test for statistically significant variations in reporting perceptions between system users and management. Responses from 30 mechanics and 27 managers revealed vast underreporting of reportable events and significant discrepancies in reporting perceptions based on age, work experience, and familiarity with voluntary reporting systems. Results also showed inconsistent views of justification for non-reporting. These findings were used to quantify the relative magnitudes of the identified barriers and to offer recommendations for minimizing their effect on voluntary reporting.; Thesis (M.S.)--Tufts University, 2015.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Daniel Hannon.; Committee: Thomas James, and Kurt Rever.; Keywords: Engineering, and Psychology.